Spatially resolved SO2 flux emissions from Mt Etna. Issue 14 (30th July 2016) - D'Aleo, R.; Bitetto, M.; Delle Donne, D.; Tamburello, G.; Battaglia, A.; Coltelli, M.; Patanè, D.; Prestifilippo, M.; Sciotto, M.; Aiuppa, A.
Abstract: We report on a systematic record of SO2 flux emissions from individual vents of Etna volcano (Sicily), which we obtained using a permanent UV camera network. Observations were carried out in summer 2014, a period encompassing two eruptive episodes of the New South East Crater (NSEC) and a fissure‐fed eruption in the upper Valle del Bove. We demonstrate that our vent‐resolved SO2 flux time series allow capturing shifts in activity from one vent to another and contribute to our understanding of Etna's shallow plumbing system structure. We find that the fissure eruption contributed ~50, 000 t of SO2 or ~30% of the SO2 emitted by the volcano during the 5 July to 10 August eruptive interval. Activity from this eruptive vent gradually vanished on 10 August, marking a switch of degassing toward the NSEC. Onset of degassing at the NSEC was a precursory to explosive paroxysmal activity on 11–15 August. Key Points: Records of SO2 flux emissions from Etna's individual vents allow capturing shifts in volcanic activity Vent‐resolved SO2 flux time series provide constraints on geometry of the shallow plumbing system Vent‐resolved SO2 flux time series demonstrate SO2 flux increase precursory to paroxysmal (lava fountaining) activity